Healthy lifestyles and the incidence risk and time of carotid plaque: a nationwide cohort study - Chunying Lin; Xingyi Zhang; Xin Fang; Wenyan He; Xiaoyan Zhang; Chaoqun Wu; Xueke Bai; Yang Yang; Jianlan Cui; Wei Xu; Lijuan Song; Hao Yang; et al. (BMC Public Health)
Abstract Background The association between lifestyles and carotid plaque showed heterogeneity in results across studies, which may be limited by sample size or population characteristics. In addition, there is a lack of evidence on how long healthy lifestyles delay plaque development and on the metabolic factors which are likely to mediate these associations. This study aims to investigate the impact of multiple healthy lifestyles on the risk and time of carotid plaque incidence in the early stages of atherosclerotic cardiovascular disease (CVD), and to identify the metabolic factors mediating this association. Methods We analyzed data from 43,651 participants with moderate or high risk for CVD from the ChinaHEART cohort (2014–2021), excluding those with prior carotid plaque or CVD, or incomplete data. We examined the association between non-smoking, moderate alcohol intake, sufficient leisure time physical activity (LTPA), and a healthy diet and incident carotid plaque using odds ratios (ORs) and time ratios (TRs) from repeated carotid ultrasounds, and calculated the mediation effects of metabolic factors. Results During a mean follow-up period of 1.74 ± 0.43 years, the study included 43,651 participants with a mean age of 57.76 years; 62.5% were female. Incident carotid plaque was documented in 14,698 participants (33.7%). Non-smoking (OR: 0.86 [0.80, 0.91]), moderate alcohol use (0.90 [0.84, 0.97]), sufficient LTPA (0.94 [0.90, 0.99]), and a healthy diet (0.90 [0.84, 0.97]) each independently lowered the risk of carotid plaque, with TRs indicating delays in plaque onset (1.01 to 1.06). Compliance with all four healthy lifestyles significantly reduced plaque risk (OR: 0.64) and delayed onset (TR: 1.16), with stronger effects in the high-risk group (P < 0.05). Metabolic factors varied in their mediation of lifestyle effects on plaque incidence. Conclusions Healthy lifestyles are associated with a lower risk and later onset of carotid plaque, suggesting that a primary prevention strategy focusing on multiple healthy behaviors, especially in high-risk individuals, may provide significant benefits.